2018
DOI: 10.1111/acfi.12422
|View full text |Cite
|
Sign up to set email alerts
|

Economic crisis and determinants of solvency in the insurance sector: new evidence from Spain

Abstract: This paper analyses the factors that determine the solvency of insurance companies operating in Spain. The selected time span, from 2008 to 2015, encompasses a period of economic instability characterised by record low interest rates and low or even negative economic growth. Using a dynamic panel data model, we conclude that actual solvency margins are positively related to profitability, underwriting risk and a mutual-type organisation but inversely related to size, reinsurance use, longer-tailed business and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…Based on past study in many countries that revealed various findings, the determination of factors is likely to have an impact on the solvency of Sharia Life Insurance. According to Srivastava & Ray's (2013) research, company size had a strong influence on the solvency of insurance companies in India, as did research by Abduh & Zein Isma (2017) and Abera & Yirsaw (2020), but size companies were not significant to the solvency of insurance companies in Spain, contrary to Moreno et al, (2020). Contribution growth affected the solvency of Sharia businesses in Malaysia, (Abduh & Zein Isma (2017), but Abera & Yirsaw's (2020) research suggested that contribution growth had no influence on insurance companies in Ethiopia.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Based on past study in many countries that revealed various findings, the determination of factors is likely to have an impact on the solvency of Sharia Life Insurance. According to Srivastava & Ray's (2013) research, company size had a strong influence on the solvency of insurance companies in India, as did research by Abduh & Zein Isma (2017) and Abera & Yirsaw (2020), but size companies were not significant to the solvency of insurance companies in Spain, contrary to Moreno et al, (2020). Contribution growth affected the solvency of Sharia businesses in Malaysia, (Abduh & Zein Isma (2017), but Abera & Yirsaw's (2020) research suggested that contribution growth had no influence on insurance companies in Ethiopia.…”
Section: Introductionmentioning
confidence: 94%
“…The size of a corporation is determined by its total assets. Because the average loss of big firms is easier to forecast, large insurance companies have a low likelihood of default with the same amount of capital as small insurance companies (Moreno et al, 2020). Based on this explanation, the following hypothesis is proposed: H1: The size of a company has a major impact on its solvency.…”
Section: Theoretical Basis and Hypothesis Developmentmentioning
confidence: 99%
“…Building on the results of previous research, [1][2][3][4][5][6] the "inno-diversification approach technique [7][8] with the utilization of the methods of economic interpretation of findings, functional, comparative and static analysis" [6] became the basis of the prospective analysis.…”
Section: Research Techniquementioning
confidence: 99%
“…Problems of financial stability assessment in insurance organisations attract stable scientific and practical interest. Scientists discover various connections between the statutory regulation of the sector and insurers' financial soundness [2], between the capital structure and financial stability [3], between financial stability and risks [4], between risks and digitisation [5], between capital and risks [6], etc.…”
Section: Introductionmentioning
confidence: 99%
“…In another study in Spain (Moreno, et al, 2018) to analyze the factors determining the solvency of insurance companies operating from 2008-2015, using a dynamic panel data model. The study found that actual solvency margins were positively correlated with profitability, underwriting risk, and mutual-type organization, and inversely with company size, reinsurance use, and life insurance specialization.…”
Section: Literature Reviewmentioning
confidence: 99%